2022
DOI: 10.1002/vzj2.20193
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate oxygen isotope ratios in vegetated riparian buffer strip soils

Abstract: The oxygen isotopic composition of phosphate (δ 18 O P ) in soils and surface water bodies has been used to trace terrestrial P inputs into aquatic ecosystems. However, enhanced biological activity in vegetated riparian buffer strips (VBSs) may lead to an alteration of δ 18 O P values. The objective of this study was to assess whether enhanced biological cycling of P in VBS soils can be identified using δ 18 O P values. For this purpose, we sampled temperate grassland soils at various depths along a VBS to gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
(146 reference statements)
0
10
0
Order By: Relevance
“…Due to the high reaction rate, the complete oxygen exchange between phosphate and water and the large isotope fractionation (approx. 23‰ at 20°C), the activity of pyrophosphatase is often assumed to dominate the oxygen isotope composition of phosphate in environmental systems (Bauke et al, 2022; Helfenstein et al, 2018; Tamburini et al, 2012). Indeed, multiple studies have found one or more phosphate pools in the environment (soils, waters and plants) that carried the isotope equilibrium value.…”
Section: Deviations From the Oxygen Isotope Equilibrium Between Phosp...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the high reaction rate, the complete oxygen exchange between phosphate and water and the large isotope fractionation (approx. 23‰ at 20°C), the activity of pyrophosphatase is often assumed to dominate the oxygen isotope composition of phosphate in environmental systems (Bauke et al, 2022; Helfenstein et al, 2018; Tamburini et al, 2012). Indeed, multiple studies have found one or more phosphate pools in the environment (soils, waters and plants) that carried the isotope equilibrium value.…”
Section: Deviations From the Oxygen Isotope Equilibrium Between Phosp...mentioning
confidence: 99%
“…All these studies concluded that the isotope equilibrium values in environmental phosphates can essentially be assigned to the activity of intracellular pyrophosphatases. However, there are frequently found deviations from oxygen isotope equilibrium, particularly in the soils (Bauke et al, 2022; Helfenstein et al, 2021; Pistocchi et al, 2020; Rodionov et al, 2020; Wang et al, 2021).…”
Section: Deviations From the Oxygen Isotope Equilibrium Between Phosp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological flow paths in riparian zones mix these nutritional elements with C leading to biogeochemical processes that either promote or impede the export of nutrients (Bauke et al., 2022; Hedin et al., 1998; Vidon et al., 2010). Having generally high but also strongly fluctuating water tables, redox processes at the microbial scale (see previous chapters) are especially critical in soils of riparian zones.…”
Section: Ecosystem‐scale Coupling Of Water and Nutrient Dynamicsmentioning
confidence: 99%
“…Due to the complete oxygen exchange, the high reaction rate, and the large isotope fractionation, the activity of pyrophosphatase is often assumed to dominate the oxygen isotope composition of phosphate in the soil–plant system (Bauke et al., 2021; Helfenstein et al., 2018; Tamburini et al., 2012). Hence, oxygen isotope exchange in phosphates can be used to locate hotspots of P cycling, for example, within different soil compartments (Bauke et al., 2017; Siebers et al., 2018), plant compartments (Bauke et al., 2021; Pfahler et al., 2013), or within catchments (Bauke et al., 2022; Pistocchi et al., 2017).…”
Section: Molecular‐scale Processes Incorporating Water Into Nutrient ...mentioning
confidence: 99%